2006
DOI: 10.1111/j.1745-4581.2006.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

RAPID ISOLATION AND DETECTION OF ESCHERICHIA COLI O157:H7 IN FRESH PRODUCE

Abstract: This study describes a rapid method for the isolation and detection of Escherichia coli O157:H7 present at low levels (0.04–0.4 cfu/g) in fresh salad produce. Following a short enrichment (5 h at 42C), samples were processed using Pathatrix, a novel recirculating immunomagnetic capture system, linked to real‐time polymerase chain reaction and/or selective agar plating. Processing of post‐enrichment sample aliquots (10 mL diluted 1:25) and the use of preblocked paramagnetic anti‐E. coli O157:H7 beads enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The beads might be combined with an au- tomated recirculating immunomagnetic capture system, similar to the AOAC-validated method currently in use for pooling and concentrating Escherichia coli O157:H7, Salmonella spp., or Listeria spp. (Prentice et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The beads might be combined with an au- tomated recirculating immunomagnetic capture system, similar to the AOAC-validated method currently in use for pooling and concentrating Escherichia coli O157:H7, Salmonella spp., or Listeria spp. (Prentice et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Compared to antibodies, CBD beads have similar equilibrium constants, but offer the advantage of in vitro production thus not relying on the use of laboratory animals (Loessner et al, 2002). Bead-based separation protocols are fast, are easy to perform, and have the inherent option of automation (Prentice et al, 2006). As a prerequisite for further developments, the suitability of these beads for separation of L. monocytogenes directly from raw milk rather than from the enrichment broth was thoroughly assessed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was not considered a false positive when a positive BAX result could not be confirmed. The use of immunomagnetic separation as a method of sample cleanup improves confiimation and PCR detection (10,13). BPW + n enrichment had two less Salmonella-positive BAX results (trial 1, irrigation water, 30°C) than TT enrichments.…”
Section: Detection Of Salmonella By Fda Bammentioning
confidence: 99%
“…Various studies have attempted to reduce nonspecific binding to IMS beads by a variety of techniques. Prentice and others (2006) found that a 1 : 10 of dilution of produce enrichment broths with fresh media coupled with using Pathatrix beads that had been preblocked with skim milk for IMS improved isolation of E. coli O 157:H7 on TC‐SMAC by reducing the number of background organisms on the plates. Lau and others (2006) modified the FDA BAM procedure for isolation of E. coli O157:H7 from artificially contaminated lettuce and found that many mucoid types of microorganisms bound to the E. coli O157:H7 paramagnetic beads interfered with isolation of the inoculated organisms on TC‐SMAC agar.…”
Section: Resultsmentioning
confidence: 99%